ASME 4th International Conference on Nanochannels, Microchannels, and Minichannels, Parts a and B 2006
DOI: 10.1115/icnmm2006-96100
|View full text |Cite
|
Sign up to set email alerts
|

Optical Measurement of Void Fraction and Bubble Size Distributions in a Microchannel

Abstract: An optical measurement system was developed to investigate gas-liquid two-phase flow characteristics in a circular microchannel of 100 μm diameter. By using multiple optical fibers and infrared photodiodes, void fraction and gas plug and liquid plug lengths, and their velocities were measured successfully. The probes responded to the passage of gas and liquid phases through the microchannel adequately so that the time-average void fraction could be obtained from the time fraction for each phase. Also, by cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Which type describes well the gas hold‐up is mainly dependent on the channel size . Besides the channel size, there are many factors that can affect the gas hold‐up such as fluid property, experimental setup, channel length, and channel geometry . This study investigated the impact of the system pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Which type describes well the gas hold‐up is mainly dependent on the channel size . Besides the channel size, there are many factors that can affect the gas hold‐up such as fluid property, experimental setup, channel length, and channel geometry . This study investigated the impact of the system pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Figs. [16][17][18] show the estimates and measurements of five successive gas and liquid slug lengths in Table 2 Estimates and measurements of gas and liquid slug lengths. Table 2, it is confirmed that L G and L L in all cases are estimated accurately by using the proposed estimation method.…”
Section: Verification Of Developed Estimation Methodsmentioning
confidence: 99%
“…In the digital fiber-optic sensor unit, two neighboring optical probes are set along the flow direction at 4 mm interval. Using the signals from two optical probes placed a certain interval, the two signals can be cross-correlated to determine the time lag and then yield instantaneous superficial velocity of slug flow and slug lengths of gas and liquid [18]. According to the obtained superficial velocity, time-varying Q G and Q L are calculated.…”
Section: Gas-liquid Slug Flow In T-shaped Microreactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies of bubble dynamics in the microfluidic circumstances with numerical methods were also suggested [27,28]. Some other properties of the gas-liquid two-phase flow in microchannels were studied under different circumstances [29,30]. From the researches above, fundamental explanations and preliminary conclusions for the influence of gas bubbles in microfluidic systems could be drawn.…”
Section: Introductionmentioning
confidence: 97%